Genetic redundancy of 4‐hydroxybenzoate 3‐hydroxylase genes ensures the catabolic safety of Pigmentiphaga sp. H8 in 3‐bromo‐4‐hydroxybenzoate‐contaminated habitats. (4th August 2022) - Chen, Kai; Xu, Xihui; Yang, Muji; Liu, Tairong; Liu, Bin; Zhu, Jianchun; Wang, Baozhan; Jiang, Jiandong
Abstract: Genetic redundancy is prevalent in organisms and plays important roles in the evolution of biodiversity and adaptation to environmental perturbation. However, selective advantages of genetic redundancy in overcoming metabolic disturbance due to structural analogues have received little attention. Here, functional divergence of the three 4‐hydroxybenzoate 3‐hydroxylase (PHBH) genes ( phbh1~3 ) was found in Pigmentiphaga sp. strain H8. The genes phbh1/phbh2 were responsible for 3‐bromo‐4‐hydroxybenzoate (3‐Br‐4‐HB, an anthropogenic pollutant) catabolism, whereas phbh3 was primarily responsible for 4‐hydroxybenzoate (4‐HB, a natural intermediate of lignin) catabolism. 3‐Br‐4‐HB inhibited 4‐HB catabolism by competitively binding PHBH3 and was toxic to strain H8 cells especially at high concentrations. The existence of phbh1 / phbh2 not only enabled strain H8 to utilize 3‐Br‐4‐HB but also ensured the catabolic safety of 4‐HB. Molecular docking and site‐directed mutagenesis analyses revealed that Val199 and Phe384 of PHBH1/PHBH2 were required for the hydroxylation activity towards 3‐Br‐4‐HB. Phylogenetic analysis indicated that phbh1 and phbh2 originated from a common ancestor and evolved specifically in strain H8 to adapt to 3‐Br‐4‐HB‐contaminated habitats, whereas phbh3 evolved independently. This study deepens our understanding of selective advantages of genetic redundancy in prokaryote's metabolic robustness and reveals the factors driving the divergent evolution of redundant genes in adaptation to environmental perturbation.